Acute regulation of apical ABC transporters in the gut: potential influence on drug bioavailability - Domínguez, Camila Juliana; Tocchetti, Guillermo Nicolás; Rigalli, Juan Pablo; Mottino, Aldo Domingo (Pharmacological research, 2021)
The extensive intestinal surface offers an advantage regarding nutrient, ion and water absorptive capacity but also brings along a high exposition to xenobiotics, including drugs of therapeutic use and food contaminants. After absorption of these compounds by the enterocytes, apical ABC transporters play a key role in secreting them back to the intestinal lumen, hence acting as a transcellular barrier. Rapid and reversible modulation of their activity is a subject of increasing interest for pharmacologists. On the one hand, a decrease in transporter activity may result in increased absorption of therapeutic agents given orally. On the other hand, an increase in transporter activity would decrease their absorption and therapeutic efficacy. Although of less relevance, apical ABC transporters also contribute to disposition of drugs systemically administered. This review article summarizes the present knowledge on the mechanisms aimed to rapidly regulate the activity of the main apical ABC transporters of the gut: multidrug resistance protein 1 (MDR1), multidrug resistance-associated protein 2 (MRP2) and breast cancer resistance protein (BCRP). Regulation of these mechanisms by drugs, drug delivery systems, drug excipients and nutritional components are particularly considered. This information could provide the basis for controlled regulation of bioavailability of therapeutic agents and at the same time would help to prevent potential drug-drug interactions.